Protective Effects of Costunolide Against D-Galactosamine and Lipopolysaccharide-Induced Acute Liver Injury in Mice - Mao, Jingxin; Yi, Man; Wang, Rui; Huang, Yuanshe; Chen, Min (Frontiers in Pharmacology, 2018)
Costunolide, a sesquiterpene isolated from Vladimiria souliei (Franch.) Ling, is known to exhibit anti-inflammatory, anti-viral, and anti-tumor activities. However, the effects of costunolide on liver injury are poorly understood. The current study aimed to investigate the hepatoprotective effects of costunolide against lipopolysaccharide and D-galactosamine-induced acute liver injury in mice. The results indicated that costunolide (40 mg/kg) could significantly improve the pathological changes of hepatic tissue, reduced the lipopolysaccharide and D-galactosamine-induced increases of alanine aminotransferase (from 887.24±21.72 to 121.67±6.56 IU/L) and aspartate aminotransferase (from 891.01±45.24 to 199.94±11.53 IU/L) activities in serum. Further research indicated that costunolide significantly reduced malondialdehyde content (from 24.56±1.39 to 9.17±0.25 nmol/ml) and reactive oxygen species (from 203.34±7.68% to 144.23±7.12%), increased the activity of anti-oxidant enzymes superoxide dismutase (from 153.74±10.33 to 262.27±8.39 U/ml), catalase (from 6.12±0.30 to 12.44±0.57 U/ml) and total anti-oxidant capacity (from 0.64±0.06 to 6.29±0.11 U/ml) in hepatic tissues. Western blot results revealed that costunolide trigger the anti-oxidative defense system by inhibiting kelch-like ECH-associated protein 1 and nuclear factor-related factor 2 (cytosol), increasing nuclear factor-related factor 2 (nucleus), heme oxygenase-1 and NAD (P) H quinone oxidoreductase 1 activity. Moreover, costunolide significantly decreased the protein expression of pro-inflammatory cytokines including interleukin 1β, interleukin 6, and tumor necrosis factor. Pretreatment with costunolide could reduce the expression of toll-like receptor 4, myeloid differentiation factor 88, p65 (Nucleus), phosphorylated IκB kinase α/β, inhibitor of nuclear factor kappa-B kinase, inhibitor kappa Bα, and prevent the expression of phosphorylated inhibitor kappa B kinase which repressed translocation of p65 from cytoplasm to nucleus. In addition, pretreatment with costunolide also inhibited hepatocyte apoptosis by reducing the expression of B-cell lymphoma 2 associated X, cytochrome C, cysteinyl aspartate specific proteinase 3, cysteinyl aspartate specific proteinase 8 and cysteinyl aspartate specific proteinase 9, as well as is increased B-cell lymphoma 2. The protective effects of costunolide against lipopolysaccharide and D-galactosamine -induced acute liver injury might attributed to its anti-oxidative activity in nuclear factor-related factor 2 signaling pathways, anti-inflammatory suppression in nuclear factor-kappa B signaling pathways, and inhibition of hepatocyte apoptosis. Thus, costunolide may be a potential therapeutic agent in attenuating acute liver injury in the future.